Harmonisation Between DSN-MUI Fatwas and OJK Regulations: Towards an Innovative and Inclusive Sharia-Compliant Fintech Ecosystem in Indonesia - Suaidi, Suaidi; Mun'im, Zainul; Astuti, Sriyati Dwi; Riyadi, Ivan; Khabibah, Siti; Huda, Nurul (Mazahib, 2025)
Since 2018, Sharia FinTech in Indonesia has grown significantly through platform-based innovations combining Islamic contracts and digital technology. The development of this industry is influenced by ongoing efforts to harmonize DSN-MUI fatwas with OJK regulations, aiming to enhance Sharia compliance and legal certainty. Through DSN-MUI fatwas (2008–2021) and POJK regulations (2016, 2022), religious and state authorities have worked to enhance legal certainty and consumer protection in the Sharia-based digital finance sector. This study adopts a qualitative approach through literature-based document analysis to examine how DSN-MUI fatwas and OJK regulations contribute to developing the Sharia FinTech industry. The research findings indicate that while fatwas offer normative guidance for Sharia compliance, challenges persist in areas such as financial literacy, technological readiness, and regulatory oversight effectiveness. The findings suggest a need for clearer regulations, improved public education, and more effective use of technology to enhance the transparency and efficiency of Sharia financial services. Stronger collaboration between financial regulators and religious institutions can improve the capacity of Sharia FinTech to support financial inclusion and contribute to sustainable growth in the Islamic economy.